DEVELOPMENT OF A SOFTWARE PACKAGE FOR DETECTING AND RECOGNIZING ANOMALOUS OBJECTS FROM DRONE IMAGES (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores the development of a software complex designed for detecting and recognizing anomalous objects in drone imagery. With the increasing role of drones in security, environmental monitoring, disaster management, and infrastructure inspection, accurate anomaly detection is becoming a critical task. The proposed system integrates computer vision, machine learning, and artificial intelligence techniques to identify unusual patterns, objects, or behaviors from aerial images. The article presents a review of the literature, outlines the methodological framework, and discusses implementation challenges, experimental results, and future directions.